Level of awareness on the sustainable development goals among Indian youth: Empirical evidence from Northern India - Sharma, Shraddha; Manani, Preeti; Thakwani, Monika; Satsangi, Rupali; Sharma, Priti; Jamwal, Dolly (Edelweiss Applied Science and Technology, 2024)
In India, government has made many policies and plans to contribute in the attainment of SDGs but being a developing nation with a large population and vast geographical expanse, the attainment of SDGs is a big task. In the 2022 Global Index of SDGs, India ranked 121 out of 163 countries. The present research's objective was to measure the awareness among universities students. Two stage cluster sampling was used for sample selection. In the first stage, 4 cities from the Northern part of India were selected and in second stage, from each city, selection of subjects was done. 546 subjects were contacted, and 335 participated. Survey was conducted using questionnaires (Odoom, Mensah, Dick‑Sagoe, Lee, Opoku & Obeng‑Baah, 2024). The scale has questions related to all the SDGs. Results showed that subjects had moderate awareness about SDG5, SDG6, SDG7, SDG9, SDG13 and SDG15 with the respective mean score (Mean 3.32, 3.77, 3.80, 3.27, 3.79, & 3.27) and had low awareness for SDG10, SDG11, SDG16, and SDG17 with the respective mean score (Mean 2.95, 2.86, 2.95, & 2.86). Results showed significant difference in the SDGs awareness among male and female. For SDG2, SDG3, SDG4, SDG9, SDG14, SDG15 and SDG17, the awareness was higher in male (respective mean rank score182.80, 181.76, 176.29, 181.80, 217.26, 184.95, 194.08) than female (respective mean rank score 152.01, 153.12, 159.04, 153.09, 122.42, 149.68, 139.81). For SDG5, SDG6, SDG7, SDG10, SDG11, SDG12, SDG13, SDG16, the awareness was higher in female (respective mean score 224.19, 224.19, 196.48, 198.99, 211.51, 205.13, 219.52, 205.25) in comparison to male (respective mean score 116.01, 115.01, 141.65, 139.32, 127.74, 133.64, 120.33, 133.53). Results of the present research also imply the role of social structure in SDGs awareness and highlight the need to introduce some programs to promote the discussion on SDGs in every classroom.